Impact of dose and duration of therapy on dexamethasone pharmacokinetics in childhood acute lymphoblastic leukaemia—a report from the UKALL 2011 trial. (October 2019) - Jackson, Rosanna K.; Liebich, Martina; Berry, Philip; Errington, Julie; Liu, Jizhong; Parker, Catriona; Moppett, John; Samarasinghe, Sujith; Hough, Rachael; Rowntree, Clare; Goulden, Nick J.; Vora, Ajay; et al.
Abstract: Introduction: The use of dexamethasone in acute lymphoblastic leukaemia therapy contributes to short- and long-term toxicities. The UKALL 2011 randomised trial investigated whether a more intense dexamethasone dose (10 mg/m 2 /d x 14d, short vs 6 mg/m 2 /d x 28d, standard) would lead to a more rapid cytoreduction and reduced adverse effects associated with longer durations of steroids in induction. The impact of dose and duration on dexamethasone pharmacokinetics was investigated. Methods: Blood samples were obtained on one of the first three and last three days of induction dexamethasone dosing at time points up to 8 h after oral administration. Plasma dexamethasone levels were quantified in 1084 plasma samples obtained from 174 children and a population pharmacokinetic model developed. Results: Drug exposure varied significantly between patients, with a >12-fold variation in AUC0–12h values and a marked overlap in dexamethasone exposures between dose levels. Intuitively, AUC0–12h was significantly higher with short dosing (10 mg/m 2 /d), but cumulative exposure was significantly higher with standard dosing over 28 days, after a higher cumulative dose. Concomitant rasburicase administration was associated with a 60% higher dexamethasone clearance. Day 8 bone marrow response was comparable between dosing arms, but those with <5% blast count exhibited a greater mean dexamethasone exposure than those with >5%. No statistical differences were observed between arms in terms of steroid-related toxicity or minimal residual disease at the end of induction. Conclusion: The potential significance of dexamethasone AUC0–12h on early response and higher cumulative exposure on the standard arm suggest that duration of therapy and exposure may be more important factors than absolute dose from a clinical pharmacology perspective. Highlights: The impact of dose and duration on dexamethasone pharmacokinetics has been investigated in ALL patients. Dexamethasone levels were quantified in 1084 plasma samples obtained from 174 children. Marked interpatient pharmacokinetic variability was observed between patients on different dose levels. Patients with a day 8 blast count <5% had significantly higher dexamethasone exposures than those with a blast count >5%. Duration of dexamethasone therapy may be more important than absolute dose from a clinical pharmacology perspective.